Author Topic: Solving this  (Read 3061 times)

0 Members and 1 Guest are viewing this topic.

Offline aeTIos

  • Nonbinary computing specialist
  • LV12 Extreme Poster (Next: 5000)
  • ************
  • Posts: 3915
  • Rating: +184/-32
    • View Profile
    • wank.party
Solving this
« on: November 21, 2012, 05:53:23 am »
So yeah, I had a math exam today and the last question was this: f(x) = x*2^(2x+3), there is a horizontal line y=q that intersects the y axis in A and f(x) in B and C with AB:BC = 1:2. Calculate q in 2 decimals.
graph:

I didn't finish it during the exam (too bad) but this is what I came at afterwards:
f(-x) = f(-3x)  ; final answer is in -x, for why take a look at the graph
-x*2^(-2x+3)=-3x*2^(-6x+3)
-x*2^(-2x)*8=-3x*2^((-2x)^3)*8
-x*2^(-2x)=-3x*2^((-2x)^3)
;;substitute p for 2^(-2x)
-xp=-3xp^3
3p^2=1
p^2=1/3
p=sqrt(1/3)
2^(-2x) = sqrt(1/3)
log2(sqrt(1/3))=-2x
-x = log2(sqrt(sqrt(1/3)))
now input log2(sqrt(sqrt(1/3))) in f and you get y=~-1.83 so q = -1.83
Did I solve this right? Are there faster or better ways to do it?
« Last Edit: November 21, 2012, 06:34:13 am by aeTIos »
I'm not a nerd but I pretend:

Offline jacobly

  • LV5 Advanced (Next: 300)
  • *****
  • Posts: 205
  • Rating: +161/-1
    • View Profile
Re: Solving this
« Reply #1 on: November 21, 2012, 06:21:37 am »
-x 2-2x+3=-3x 2-6x+3
2-2x+3/2-6x+3=-3x/-x
2(-2x+3)-(-6x+3)=3 ; x!=0
log2(3)=(-2x+3)-(-6x+3)
log2(3)=4x
x=log2(3)/4

Offline aeTIos

  • Nonbinary computing specialist
  • LV12 Extreme Poster (Next: 5000)
  • ************
  • Posts: 3915
  • Rating: +184/-32
    • View Profile
    • wank.party
Re: Solving this
« Reply #2 on: November 21, 2012, 06:24:57 am »
Ah yeah I see, thanks :D
Actually what I did was in fact the same but with more steps, especially substitution. (which I use a lot since I can't see 2xx as one number D:)
« Last Edit: November 21, 2012, 06:25:14 am by aeTIos »
I'm not a nerd but I pretend:

Offline ElementCoder

  • LV7 Elite (Next: 700)
  • *******
  • Posts: 611
  • Rating: +42/-2
    • View Profile
Re: Solving this
« Reply #3 on: December 20, 2012, 04:06:56 am »
I don't even understand anymore why to solve f(-x)=f(3x) O_O
[edit] sorry for the kind-of necropost :P
« Last Edit: December 20, 2012, 04:07:20 am by ElementCoder »

Some people need a high five in the face... with a chair.
~EC